A perspective on the development of hemispheric specialization, infant handedness, and cerebral palsy. (June 2020) - Ferre, Claudio L.; Babik, Iryna; Michel, George F.
Abstract: Cerebral Palsy (CP), a common form of neurological pediatric disability, results from pre- or perinatal brain injury. Although there is growing evidence of the efficacy of motor learning-based therapies, several factors interact to produce variability in impairment and limit the effectiveness of these therapies. The variability of hand function present in children with CP indicates that a range of developmental pathways must contribute to the manifestation of individually unique characteristics of impairment. Despite two decades of progress using therapies derived from understanding the mechanisms controlling hand function, very little is known about the sensorimotor experiences occurring during development that likely shape later functional problems for children with CP. In this "perspective" paper, we propose that the study of the development of motor skills in typically developing infants may reveal experiential factors potentially important for creating remedial therapies for children with CP. Specifically, we use the development of infant handedness, a model of hemispheric specialization of function, as an example of how self-generated experiences and sensorimotor feedback can shape the development of limb control and hemispheric specialization. We illustrate how early sensorimotor asymmetries concatenate into pronounced differences in skill between the two hands. We suggest that this model of infant handedness provides a framework for studying the individual differences manifested in children with CP. These differences likely arise from aberrant sensorimotor experiences created by sensorimotor circuits disrupted by the early brain injury. We conclude that knowledge of the developmental events, including subtle motor behaviors, that shape sensorimotor pathways, can improve treatment options for children with CP.